Serum CD14 concentration is associated with obesity and insulin resistance in non-diabetic individuals - Yea Eun Kang; Kyong Hye Joung; Ji Min Kim; Ju Hee Lee; Hyun Jin Kim; Bon Jeong Ku (Journal of International Medical Research, 2022)
Objective CD14 is a lipopolysaccharide-binding protein that serves as a marker of monocytes. The role of circulating CD14 in patients with obesity without diabetes remains unknown. Here, we characterized the relationships between serum CD14 concentration and metabolic parameters related to diabetes and obesity. Methods We performed an observational, prospective case–control study. Eighty participants were evaluated: 26 drug-naïve patients with type 2 diabetes mellitus and 54 healthy individuals. We compared the circulating CD14 concentration and metabolic parameters of the participants with and without diabetes. Results The circulating CD14 concentration did not significantly differ between the two groups, but was lower in participants with obesity than in lean controls. No significant associations existed between CD14 concentration and metabolic parameters in the participants with diabetes, but in those without diabetes, the circulating CD14 concentration significantly negatively correlated with body mass index; waist circumference; the concentrations of fasting insulin, 2-hour post-load glucose, 2-h post-load insulin, and low-density lipoprotein-cholesterol; homeostasis model of assessment (HOMA) of insulin resistance; and HOMA beta-cell function. Conclusions This is the first study to show associations of serum CD14 concentration with metabolic parameters in non-diabetic individuals. Circulating CD14 may represent a useful biomarker of metabolic dysfunction in non-diabetic individuals.